2020
DOI: 10.1186/s12889-020-09294-0
|View full text |Cite
|
Sign up to set email alerts
|

Mid-upper arm circumference as an indicator of underweight in adults: a cross-sectional study from Nepal

Abstract: Background Undernourished people have an increased risk of premature mortality from both infectious and non-communicable diseases. Aside from screening purposes, assessment of nutritional status is a useful tool in management and evaluation of various chronic diseases. Body-Mass-Index (BMI) is today the most commonly used marker of nutritional status however, this method presents a challenge in many low resource settings and immobile patients. Mid-upper arm circumference (MUAC) is another anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 13 publications
1
18
1
2
Order By: Relevance
“…Both MUAC cut-offs, <24 and <25 cm, identified more Tanzanian, male and the elderly (≥65 years) farmers with underweight, but again with a consequently lower specificity. A recent study in 302 female and male chronically ill and healthy adults from two urban public hospitals in Nepal suggested a MUAC cut-off of 24.5 cm (according to highest Youden's Index) for both sexes to identify underweight [33].…”
Section: Discussionmentioning
confidence: 99%
“…Both MUAC cut-offs, <24 and <25 cm, identified more Tanzanian, male and the elderly (≥65 years) farmers with underweight, but again with a consequently lower specificity. A recent study in 302 female and male chronically ill and healthy adults from two urban public hospitals in Nepal suggested a MUAC cut-off of 24.5 cm (according to highest Youden's Index) for both sexes to identify underweight [33].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a MUAC of 24 cm was proposed as appropriate in a study from the Southern India (Rodrigues et al 1994), among the Oraon tribal men from another eastern Indian state (Chakraborty et al 2011), and also among the slum dwellers of eastern India (Chakraborty et al 2009a(Chakraborty et al , 2009c. Thorup et al (2020) reported that MUAC of 24.5 cm was found to be the most appropriate to predict CED status together for both men and women in Nepal. On the basis of such findings, indicating higher MUAC cut off values than the universally proposed values by WHO, it was also argued that such tendency was perhaps due to the diverse ethnic origin and variation in body fat patterning and differences in the relationship between BMI and body fat across populations (Chakraborty et al 2009c).…”
Section: Discussionmentioning
confidence: 99%
“…Considering such operational problem with BMI, the mid-upper arm circumference (MUAC) is strongly recommended as an alternative measurement to assess undernutrition in infants, children and adults WHO, UNICEF 2019) and even in pregnant women (Fakier et al 2017). It is mostly because MUAC is a simple, non-invasive measurement requiring simple equipment, i.e., a tape measure, and thus, suitable for epidemiological and clinical settings, particularly, in resource-limited set up (Das et al 2018;Thorup et al 2020;WHO 2004). Besides, MUAC shows consistently a high correlation with BMI across age (Das et al 2018;Tang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown a significant correlation between MUAC and BMI, it is known that individuals with low MUAC are likely to have a low BMI. 4,6,[18][19][20][21][22][23] Research conducted by Brito et al 8 on 1373 inpatients at a hospital in Spain, showed that there was a correlation between BMI and MUAC with r = 0.78 (p <0.001). The cut-off point value for detecting malnutrition obtained from this study was 22.5 cm for both men and women.…”
Section: Research About Muac Cut-off Point For Detecting Malnutritionmentioning
confidence: 98%